INOVASI DALAM ORGANISASI PENDIDIKAN - Aisyah, Neng; Khotima, Husnul; Ismail, Fajri; Karoma; Mahda lewis, Azizul (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research aims to examine various aspects of innovation in educational organizations, including the definition, importance of innovation, factors that encourage and inhibit innovation, as well as strategies and best practices in managing innovation. The research method used is literature study, with a focus on descriptive analysis from various relevant library sources. The research results show that innovation in educational organizations is very important to improve the quality of learning, develop more effective teaching methods, and create a conducive learning environment. Support from leadership, active participation of organizational members, a culture that supports innovation, and availability of resources are factors that encourage innovation. On the contrary, uncertainty of goals, lack of support and incentives, and resistance to change are the main obstacles. An effective strategy includes an innovation-oriented vision and mission, supportive leadership, collaboration with various parties, and the use of educational technology. Best practices include building a culture of innovation, training and professional development, use of data for evaluation, stakeholder participation, and ongoing evaluation.